Diatom diversity and distribution in Neotropical karst lakes under anthropogenic stress - Margarita Caballero; Gabriela Vázquez; Ana Carolina Ruiz-Fernández; Javier Alcocer; Lucy Natividad Mora-Palomino (PLoS ONE, 2025)
Lake degradation is an important environmental problem in the Neotropics, where rapid population growth is leading to increasing human impact. However, baseline studies in these lakes are still scarce. This study focussed on the hydrochemistry, trophic status and analysis of diatom diversity and ecological distribution in Neotropical karst lakes in southern Mexico, presenting a high-resolution paleolimnological reconstruction of changing hydrochemical and trophic characteristics since the late 1950s based on multiproxy analysis of a sequence dated by 210Pb and 14C. Four of the sixteen freshwater lakes had higher salinity (300−500 mg L-1), sulphates, turbidity and eutrophic conditions. These impacted, eutrophic to hypertrophic ecosystems receive soil-derived sediment, organic matter, urban and agricultural effluents through river inflow. Two diatom taxa were characteristic of these impacted lakes (Aulacoseira granulata var. angustissima and Stephanocyclus meneghinianus) while eight were preferentially present in the lower-salinity, oligo-mesotrophic lakes. Some of the lower-salinity taxa have restricted Neotropical karst distributions (Cyclotella petenensis, Discostella sp., Mastogloia calcarea and Planothidium sp.), and are in danger of local extirpation as hydrochemical changes and eutrophication increase. The beta diversity (βw) of the full data set was low (2.6), driven mostly by the hydrochemical and trophic status differences between the four most impacted lakes and the rest. Paleolimnological analysis allowed us to determine that the currently impacted lakes previously had lower salinity and trophic conditions, comparable with the currently non-impacted lakes. In Lake Peñasquito, increasing erosion during the 1970s was associated with the first appearance (1980s) and gradual increase of diatom taxa characteristic of lake degradation, and a critical transition point was observed in the diatom assemblages by ca. 2008.